Determinants Factors of Husband’s Participation in Prenatal Class - Sri Widatiningsih; Ayuningtiyas Ayuningtiyas; Mundarti Mundarti (Politeknik Kesehatan Kementerian Kesehatan Semarang, 2023)
Pregnancy is an important transition period in the biochemical, physiological and anatomical changes of the female body. Prenatal Class as a forum for pregnant women and their families to obtain information together and learn about maternal and child health as the main social support during pregnancy. Men who feel unprepared for fatherhood tend to be fathers who are not involved early, resulting in a difficult transition into parenthood, less likely to become committed fathers. This study aims to analyze the factors that influence the low participation of husbands in the Prenatal Class. This type of research is analytic research with a cross sectional approach. Population of husbands of pregnant women class participants in the city of Magelang. The sample in this study used the cross-sectional sample size formula and obtained a total sample of 48 people, taken using purposive sampling using a questionnaire instrument. Statistical analysis with Spearman Rho correlation test. Interpretation of statistical test results is based on the p value, the strength and direction of the correlation. The results of the analysis in testing the hypothesis by looking at the significance value, there is a significant influence on the factors of education (0.000), employment (0.000), socialization (0.009) and there is no effect of age (0.774), number of pregnancies (0.494) on husband's participation in class pregnant mother. Factors of education, employment, and socialization affect participation, while age, number of pregnancies do not affect husband's participation in classes for pregnant women.